2021
DOI: 10.1021/acs.biochem.0c00922
|View full text |Cite
|
Sign up to set email alerts
|

Danio rerio Oocytes for Eukaryotic In-Cell NMR

Abstract: Understanding how the crowded and complex cellular milieu affects protein stability and dynamics has only recently become possible by using techniques such as in-cell nuclear magnetic resonance. However, the combination of stabilizing and destabilizing interactions makes simple predictions difficult. Here we show the potential of Danio rerio oocytes as an in-cell nuclear magnetic resonance model that can be widely used to measure protein stability and dynamics. We demonstrate that in eukaryotic oocytes, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 84 publications
0
46
0
Order By: Relevance
“…150,151 In cells, where translational diffusion is further reduced, the approach has been pushed to its limits by Dobson and Christodoulou, who showed that 15 Nor 13 C-edited diffusion experiments allowed one to study the diffusion behavior of proteins in bacteria, even in the presence of interactions with cellular components, and could be employed as effective filters to distinguish intracellular from extracellular proteins. 152 In addition to the above approaches relying on 13 C and 15 N, 19 F NMR has also been applied to probe the conformational dynamics and diffusion of macromolecules in living cells. 19 F T 1 and T 2 , measured by inversion recovery and Carr-Purcell-Meiboom-Gill (CPMG), respectively, allow probing the nanosecond time-scale motions of a fluorinated protein both in the folded and in the unfolded state, as shown in bacterial cells by Pielak and Li.…”
Section: Nmr Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…150,151 In cells, where translational diffusion is further reduced, the approach has been pushed to its limits by Dobson and Christodoulou, who showed that 15 Nor 13 C-edited diffusion experiments allowed one to study the diffusion behavior of proteins in bacteria, even in the presence of interactions with cellular components, and could be employed as effective filters to distinguish intracellular from extracellular proteins. 152 In addition to the above approaches relying on 13 C and 15 N, 19 F NMR has also been applied to probe the conformational dynamics and diffusion of macromolecules in living cells. 19 F T 1 and T 2 , measured by inversion recovery and Carr-Purcell-Meiboom-Gill (CPMG), respectively, allow probing the nanosecond time-scale motions of a fluorinated protein both in the folded and in the unfolded state, as shown in bacterial cells by Pielak and Li.…”
Section: Nmr Methodsmentioning
confidence: 99%
“…Biomolecular NMR spectroscopy typically relies on spin-1/2 nuclides of biologically abundant atoms: 1 H, 13 C, and 15 N. Given the low natural abundance of 13 C (1.1%) and 15 N (0.4%) isotopes, the molecules of interest must be isotopically enriched for the NMR analysis. This poses further requirements when preparing samples for in-cell NMR.…”
Section: Isotopic Labelingmentioning
confidence: 99%
See 3 more Smart Citations